2001
DOI: 10.1099/00207713-51-5-1867
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentiphaga kullae gen. nov., sp. nov., a novel member of the family Alcaligenaceae with the ability to decolorize azo dyes aerobically.

Abstract: NOTET with the name Pigmentiphaga kullae gen. nov., sp. nov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 14 publications
3
14
0
1
Order By: Relevance
“…Possivelmente essa resistência é induzida pela capacidade de adaptação dessas bactérias em ambientes contaminados pelo MFA, permitindo que utilizem essa substância como fonte de carbono e energia (Blümel et al 2001, Firsova et al 2009). Resultados semelhantes foram observados por Gregg et al (1998) que inocularam em ovinos a bactéria ruminal, Butyrivibrio fibrisolvens modificada geneticamente com um gene que codifica a produção da enzima fluoroacetato dehalogenase, obtido a partir de uma espécie de Moraxella, comprovando que os ovinos inoculados eram resistentes a doses maiores de MFA do que os animais controles.…”
Section: Discussionunclassified
“…Possivelmente essa resistência é induzida pela capacidade de adaptação dessas bactérias em ambientes contaminados pelo MFA, permitindo que utilizem essa substância como fonte de carbono e energia (Blümel et al 2001, Firsova et al 2009). Resultados semelhantes foram observados por Gregg et al (1998) que inocularam em ovinos a bactéria ruminal, Butyrivibrio fibrisolvens modificada geneticamente com um gene que codifica a produção da enzima fluoroacetato dehalogenase, obtido a partir de uma espécie de Moraxella, comprovando que os ovinos inoculados eram resistentes a doses maiores de MFA do que os animais controles.…”
Section: Discussionunclassified
“…Discrepancies between the original species descriptions and current data are included in parentheses. (Blumel et al, 2001;Yoon et al, 2007;and Chen et al, 2009 (Blümel et al, 2001). The closest species in another genus, Parapusillimonas granuli Ch07 T (Kim et al, 2010), showed a lower degree of sequence similarity (96.5%).…”
mentioning
confidence: 91%
“…The effluent laden water of Noyyal at Tirupur as well as effluent at waste water treatment plants have bacteria like Pseudomonas sp. and Achromobacter sp., and these bacterial species have shown potential to decolorize the dye effluent color in different studies (Bhatt et al 2005;Blumel et al 2001). Also Bacillus sp.…”
Section: Aspergillus Nigermentioning
confidence: 99%